THE ANALYSIS OF REGULAR STUDENTS’ PARENTS PERCEPTION TOWARDS INCLUSION PROGRAM - Martha Yunita, Vania; Salim, Abdul; Sunardi, Sunardi (Pusat Penelitian dan Pengembangan Rekarta Mataram, 2020)
Abstrak: Program pendidikan inklusi merupakan salah satu program pemerintah yang sedang digalakkan di Indonesia. Banyak dampak yang disebabkan oleh program ini, dampak terhadap siswa berkebutuhan khusus, siswa reguler, orangtua siswa berkebutuhan khusus, orangtua siswa reguler bahkan pendidik. Semua mempunyai pengaruh terhadap kemajuan program inklusi, orangtua siswa reguler yang diteliti disini mempunyai andil yang kurang terlihat sehingga perlu adanya penelitian terkait dengan persepsi program inklusi menurut para orangtua siswa reguler. Penelitian ini menggunakan metode pengisian angket dan wawancara sehingga hasil yang didapat tidak menjadi disalah artikan. Hasil dari penelitian ini menyatakan persepsi orangtua siswa reguler terhadap program inklusi sangat positif namun terdapat beberapa temuan terkait dengan kontribusi orangtua siswa reguler terhadap program inklusi. Abstract: The inclusive education program is one of the government programs being promoted in Indonesia. There are many impacts caused by this program towards students with special needs, regular students, parents of students with special needs, parents of regular students and even educators. There are also many perceptions related to children with special needs in inclusive schools. All of them have an influence on the progress of the inclusion program. The parents of the regular students studied here have a less visible contribution so there is a need for research related to the perception of the inclusion program for the parents of regular students. This study used the questionnaire filling method and interview with the subject of the parents of regular students in the inclusive school. The results of this study stated that the parents of regular students? perceptions towards the inclusion program were very positive but there were several findings related to contributions of regular students? parents to the inclusion program